2014
DOI: 10.1080/08912963.2014.945926
|View full text |Cite
|
Sign up to set email alerts
|

A Late Pleistocene (MIS3) ungulate mammal assemblage (Los Rincones, Zaragoza, Spain) in the Eurosiberian–Mediterranean boundary

Abstract: During the Upper Pleistocene the archaeo-paleontological sites in the Iberian Peninsula are located mainly on the coasts. Here we present for the first time a paleoenvironmental proxy for Upper Pleistocene locality (MIS3) that is in the interior peninsular, in the Moncayo Massif (Zaragoza). This is actually the boundary between Mediterranean and Eurosiberian climatic-regions. The present study is based in the site ungulates: Capra pyrenaica, wich is bigger in size than current and fossil from Mediterranean are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 77 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…Spanish fossil remains attributed with certainty to the Pyrenean chamois are known since MIS 3 (Altuna , Álvarez‐Lao , Sauqué et al. ).…”
Section: Resultsmentioning
confidence: 99%
“…Spanish fossil remains attributed with certainty to the Pyrenean chamois are known since MIS 3 (Altuna , Álvarez‐Lao , Sauqué et al. ).…”
Section: Resultsmentioning
confidence: 99%
“…By comparing footprints and ungual phalanges of fossil and modern equids, we found that this generalization holds up quite well. Tridactyl equids tend to have ungual phalanges and footprints that are oval in shape and longer than wide (as in the Ukrainian print with frogs noted above where length/width ratio = 1.27), whereas monodactyl equids tend to have ungual phalanges and footprints that are more circular in shape and wider than long (see later discussion of the ‘ovality index’; see also [ 104 ], p. 17, fig. 10).…”
Section: Fossil Equid Trackways and Evidence Of A Frog In Tridactyl F...mentioning
confidence: 99%